DETERMINATION OF TOTAL FLAVONOID LEVELS ON ALPUKAT FRUIT SKIN (PERSEA AMERICANA MILL.) - Firlia Firlia; Sri Hastuti (Universitas Tadulako, 2020)
Avocados (Persea americana Mill) are fruits that originally from Mexico and Central America. It has the characteristics of green flesh on the bottom of the skin and yellowing toward the seeds with a texture that is rather soft when it is ripe. Skin color varies, some are green because of chlorophyll or black content due to anthocyanin pigments. This study aimed to determine the total levels of flavonoids in the skin of avocados that were green and black. Determination of total flavonoid levels used a UV- Vis spectrophotometer. The results showed that an analysis of water content was 5.306% for green avocado skin and 7.327% for black avocado skin. The analysis of total flavonoid levels at a wavelength of 437 nm obtained respectively, the average yield was 54,950 mg/100g for green avocado skin and 29,519 mg/100g for black avocado skin. The results of this study are expected to be able to attract the interest of the community to cultivate green and black avocado plants. especially in the area of Central Sulawesi.